Characterization, tissue distribution of apela and periprandial, fasting and refeeding changes of apela mRNA in Siberian sturgeon Acipenser baerii. Issue 4 (24th September 2018) - Tang, Ni; Hao, Jin; Zhang, Xin; Wu, Yuan B.; Wang, Shu Y.; Qi, Jin W.; Tian, Zhen Z.; Wang, Bin; Chen, Hu; Chen, De F.; Li, Zhi Q.
Abstract : Apela identified from zebrafish Danio rerio for the first time in 2013 is a novel endogenous peptide ligand for the apelin receptor. To study the role of apela in regulating fish feeding, the complementary (c) DNA sequence of apela of Siberian sturgeon Acipenser baerii was cloned for the first time. The apela cDNA fragment of 836 bp was obtained by cloning. The open reading frame (ORF) of apela was 165 bp encoding a 54 amino acid, including 22 amino acids signal peptide and two proteolytic sites. Phylogenetic tree analysis showed that A. baerii apela was clustered with mammalian and amphibian sequences. A. baerii apela messeger (m)RNA was widely distributed in 11 tissues related to feeding, with high expressions in brain, oesophagus and stomach, especially in the brain. The level of apela mRNA in brain increased significantly after feeding. On the first day of fasting, apela expression in brain was significantly lower than that of the fed group, but after fasting for 3–15 days, the expression of apela in A. baerii brain was significantly higher than that in the fed group. After refeeding apela mRNA expression was obviously reduced. These results suggest that apela plays a bidirectional role in feeding regulation of A. baerii, which may serve as a short‐term satiation factor and a long‐term hunger factor.